An integrated multi stage, multi criteria analysis on psychical empowerment of employees under different leaderships â€“ a comparative study - N.G. Sreenivas, J; Koneru, Kalpana (International Journal of Engineering and Technology, 2018)
Leadership is the corner stone of an enterprise for its vision, mission and organic and inorganic growth. Employees are invaluable assets to an enterprise. However, it is true only when the actions of leadership and workforce are aligned to the vision and mission of the enterprise. An important proposition is â€œleadership style has its influence on psychological empowerment and job satisfaction of employeesâ€. This paper makes an empirical study of different leadership styles not only to know whether the proposition is affirmative but also its dynamics for each leadership style. It is achieved by investigating hypotheses associated with the proposition to add more value and clarity to the re-sults. This research is carried out in educational domain where random sampling is made among professors and head of the departments in two Indian universities named Vignan and KLU. The two-fold study consisting of secondary and primary research methods reveal interest-ing insights. Quantitative research method, survey with a well-defined questionnaire based on the hypotheses and sample size 126, is carried out and the results are subjected to quantitative analysis. The essence of the interpreted results is that there exists correlation between leader-ship style and psychological empowerment of employees. It is where this research adds more value to the proposition afore mentioned. The relationships among the variables such as leadership style, psychological empowerment in association with the hypotheses provide new research insights that help enterprises in the real world to adapt well suited leadership style for high productivity and organizational growth.Â Â